Teodulfa z Orleanu (750/760–821) fascynacja klasykami. Refleksje na kanwie utworu „Versus contra iudices” - Chudzikowska-Wołoszyn, Małgorzata (Studia Europaea Gnesnensia, 2012)
Theodulf of Orleansmay easily be called an arch-Christian eulogist of the antique heritage. His legacy is replete with classical influences. The emulation of the antique which may be noticed with the Visigoth scholar was nevertheless in line with the deliberately adopted method stemming from the Augustan programme. The exceptional aptitude of the poet combined with the skill of commanding language to his needs allowed him to create highly diverse and unconstrained literary pieces, where the reader finds combinations of elements taken from classical culture with the articles of faith and piety, occurring without conflict and artificiality but in harmony. “Versus contra iudices” proves that Theodulf was a master at composing anecdotal coincidence of two worlds and simultaneously, two sensitivities as well. Thanks to the gifted Visigoth, myth and classical tradition became something in the way of early medieval philosophia moralis.